Signal Integrity Analysis in Carbon Nanotube Based Through-Silicon Via - Manoj Kumar Majumder; Archana Kumari; Brajesh Kumar Kaushik; Sanjeev Kumar Manhas (Active and Passive Electronic Components)
Development of a reliable 3D integrated system is largely dependent on the choice of filler materials used in through-silicon vias (TSVs). This research paper presents carbon nanotube (CNT) bundles as prospective filler materials for TSVs and provides an analysis of signal integrity for different single- (SWCNT), double- (DWCNT), and multi-walled CNT (MWCNT) bundle based TSVs. Depending on the physical configuration of a pair of TSVs, an equivalent electrical model is employed to analyze the in-phase and out-phase delays. It is observed that, using an MWCNT bundle (with number of shells = 10), the overall in-phase delays are reduced by 96.86%, 92.33%, 78.35%, and 32.72% compared to the bundled SWCNT, DWCNT, 4-shell MWCNT, and 8-shell MWCNT, respectively; similarly, the overall reduction in out-phase delay is 85.89%, 73.38%, 45.92%, and 12.56%, respectively.